A new species of freshwater isopod (Sphaeromatidea: Sphaeromatidae) from an inland karstic stream on Espíritu Santo Island, Vanuatu, southwestern Pacific - Jaume, Damià; Queinnec, Erik (Zootaxa, 2007)
Exosphaeroides quirosi is described from a karstic stream and its associated cave sink located 390 m above sea level and 23.5 km inland from the east coast of Espíritu Santo (Vanuatu, SW Pacific ocean). This is the first purely freshwater sphaeromatid isopod reported from an oceanic island, and is a new example of colonization of an oceanic island freshwater habitat by a typically marine taxon. E. quirosi differs from any other representative of the family in the peculiar condition displayed by the exopod of pleopod 4, which has a falcate outline, is distinctly longer than the corresponding endopod, and has the medial margin of the proximal segment produced into a foliaceous endite. Seemingly, the sexual dimorphism expressed in the presence/absence of a setulose fringe on the pereopods has not been recorded in any other sphaeromatid. Even though the peculiar pleopod 4 and the fusion pattern of pleonites—with complete incorporation of pleonite 1 to rest of pleonites—could suggest a new genus to accommodate the new species, it is included here in the broad Exosphaeroma s. l. cluster, from which most freshwater sphaeromatids seem to derive. This is done with the caveat that it is incertae sedis in Exosphaeroides until such time as a comprehensive revision of Exosphaeroma and related genera has been undertaken. E. quirosi appears to be a Exosphaeroma-derived species with an unusual pleopod 4 and fusion of pleonite 1 to the remainder of the pleon; these features being here regarded as species-level apomorphies within a morphologically diverse genus.